Does mental fatigue influence the accuracy of paralympic boccia players? - Silva, D. F. d.; Costa, A. d. S.; Fortes, L. d. S.; Oliveira, S. F. d. M. (Frontiers in Sports and Active Living, 2025)
Mental fatigue (MF) is characterized by a long period of low cognitive complexity or a short period of high cognitive demand, moreover, MF decreases accuracy in the sport. Thus, the objective of this study was to examine the impact of MF on accuracy in Paralympic boccia (PB) athletes. A total of 11 PB athletes participated in the study, including 6 with cerebral palsy (CP) and 5 without CP. Each participant underwent three experimental conditions: MF, low cognitive effort (LCE), and control (C). All procedures were conducted at the athletes' training facilities. Accuracy was assessed following the experimental protocols. A generalized estimating equations (GEE) model was used to analyze the effects of time and condition. A significant time effect was observed for both the LCE (p < 0.05) and MF (p < 0.05) conditions. A condition effect was found for mental demand (LCE vs. MF; p < 0.05). Regarding accuracy, no condition effect was observed for the 3, 6, and 9-m distances or for the total score (p > 0.05). In conclusion, the present study demonstrated that LCE and mental fatigue do not negatively affect the accuracy of PB athletes.